Study of the dispersion of Cloisite 10A in recycled polyethylene terephtalate by extrusion (2017)
This research focuses on clay dispersion of commercial Cloisite 10A in recycled PET (RPET) to improve the properties of recycled polymer lost in the reprocessing of materials, specifically during extrusion. Varying mixtures of RPET/Cloisite 10A were prepared in a single screw extruder. The mixtures obtained were reprocessed in capillary rheometer-type single screw extruder and passed through a capillary die, at high shear stress to increase the dispersion of clay in the polymer matrix. Results show physical degradation of materials. X-ray diffraction (XRD) indicated exfoliation of clay with low concentrations. Furthermore, rheology results show that viscosity rate decreases with increase in clay concentration in the mixtures. Scanning electron microscopy (SEM) reveals low dispersion of clay with an increase of concentration.